Activity and durability of electrocatalytic layers with low platinum loading prepared by magnetron sputtering onto gas diffusion electrodes. (12th November 2019) - Ivanova, Nataliya A.; Alekseeva, Olga K.; Fateev, Vladimir N.; Shapir, Boris L.; Spasov, Dmitry D.; Nikitin, Sergey M.; Presnyakov, Mikhail Yu.; Kolobylina, Natalia N.; Soloviev, Maksim A.; Mikhalev, Artem I.; Grigoriev, Sergey A.
Abstract: This article presents development of magnetron sputtering technology for catalytic Pt coating production. Low Pt-loaded gas diffusion electrodes were prepared by a single-step magnetron sputtering in different regimes. Pt and Pt-carbon films (95–97 wt% Pt) were deposited directly onto the gas diffusion layers (GDLs): carbon paper (Sigracet® 39 BC) and carbon cloths (GDL-CT, ELAT® LT 1400 W). A bipolar pulsed direct current (DC) magnetron sputtering with pulsed frequency 100 kHz was used as the method for catalysts deposition. Total Pt loading in the thin films varied in the range 0.04–0.13 mg*cm −2 . Obtained catalysts onto GDLs were investigated by scanning/transmission electron microscope (S/TEM), X-ray Absorption Near Edge Structure (XANES) and potentiodynamic methods. The deposited catalysts had a high electrochemical surface area (ECSA) and stability determined by the durability stress test (DST) method. The highest ECSA was obtained with Pt target in the pulsed (100 kHz) sputtering mode. This ECSA values were rather stable during 3000 cycles of stress-tests versus 500 cycles for Pt deposited by polyol method on the same gas diffusion layers. Highlights: Pt catalytic coatings were produced by mid-frequency pulsed DC sputtering. The electrochemical surface areas are higher in the case of pulse mode Pt sputtering. The Pt-sputtered electrodes show high stability in the course of the durability tests.